1997
DOI: 10.1021/jf960330w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modifications of β-Lactoglobulin upon Exposure to High Pressure

Abstract: Irreversible modifications in tertiary structure, surface hydrophobicity, and association state of β-lactoglobulin were studied after exposure to high pressure (600 and 900 MPa) of solutions of the protein at neutral pH and at different concentrations. Only minor irreversible structural modifications were evident even for treatments as intense as 15 min at 900 MPa. The occurrence of irreversible modifications was time-progressive at 600 MPa but was complete within 2 min at 900 MPa. The irreversibly modified pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
56
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 34 publications
18
56
0
4
Order By: Relevance
“…Dufour et al [7] found that β-Lg unfolded extensively and irreversibly at pH 7, but less extensively and reversibly at pH 3, after pressure treatment in the 150-300 MPa range. The results of several other studies [10,12,37] have indicated that unfolding of β-Lg using pressure treatments at neutral pH, increased the reactivity of the SH group, and that intermolecular disulphide bonds formed through SH/S-S interchange reactions prevented reversible unfolding. Studies performed by Hinrichs et al [11] revealed that, at the same pressure, the rate of denaturation of β-Lg was faster than that of α-La.…”
Section: Introductionmentioning
confidence: 99%
“…Dufour et al [7] found that β-Lg unfolded extensively and irreversibly at pH 7, but less extensively and reversibly at pH 3, after pressure treatment in the 150-300 MPa range. The results of several other studies [10,12,37] have indicated that unfolding of β-Lg using pressure treatments at neutral pH, increased the reactivity of the SH group, and that intermolecular disulphide bonds formed through SH/S-S interchange reactions prevented reversible unfolding. Studies performed by Hinrichs et al [11] revealed that, at the same pressure, the rate of denaturation of β-Lg was faster than that of α-La.…”
Section: Introductionmentioning
confidence: 99%
“…Using fluorescence spectroscopy, important changes in fluorescence intensity and the emission maximum of b-lactoglobulin occur between 100 and 200 MPa [14,15]. Using circular dichroism, Tedford et al [16] have shown significant changes in secondary and tertiary structures of b-lactoglobulin whereas Iametti et al [17] found no detectable changes in the secondary structure and only a 10% loss of tertiary structure even at 900 MPa. It has been also reported that reversible modifications of the structure of b-lactoglobulin by pressure treatment lead to dissociation of dimers, mainly by destabilization of hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic hydrolysis (Chobert, Bertrand-Harb, & Nicolas, 1988;Jost & Monti, 1977;Turgeon, Gauthier, & Paquin, 1991), heat treatment (Beveridge, Toma, & Nakai, 1974;Modler & Emmons, 1976;Modler & Harwalkar, 1981;Morr, 1985) and dynamic high-pressure treatment (Dickinson, Murray, & Pawlowsky, 1997;Foegeding, Davis, Doucet, & Mc Guffey, 2002;Iametti, Transidico, Bonomi, & Vecchio, 1997;Ibanoglu & Karatas, 2001;Pittia, Wilde, Husband, & Clark, 1996) have been show to effectively affect the structure and functions of whey proteins. The effect of heat treatment on the structural and chemical properties of whey proteins, commonly referred to as denaturation, has been extensively studied in the literature because it is the most commonly applied in food processing.…”
Section: Introductionmentioning
confidence: 99%